KONSEP IBADAH DALAM HINDU - Abu Bakar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
In hinduism has five subject confidences that mutually gets bearing among one by another one. Hindustanis, really gets to hold firmness with concept in its religion namely, believe to mark sense God (God), mark sense soul each creature, trusting Law because effect, trusting parturition and death, intent supreme final human, where dou man reach Moksa